A broadband MIMO antenna's channel capacity for WLAN and WiMAX applications - Raefat-Jalila El Bakouchi; Abdelilah Ghammaz (Institute of Advanced Engineering and Science, 2022)
This paper describes the findings of a research into the multiple input multiple output (MIMO) channel capacity of a broadband dual-element printed inverted F-antenna (PIFA) antenna array. The dual-element antenna array is made up of two PIFAs that are meant to fit on a teeny-tiny and small wireless communication device that runs at 5 GHz. The device's frequency range is between 3.5 and 4.5 GHz. These PIFAs are also loaded into the device during the installation process. In order to investigate the channel capacity, the ray tracing method is employed in two different kinds of circumstances. For the purpose of carrying out this analysis of the channel capacity, both the simulated and measured mutual couplings of the broadband MIMO antenna are utilized.